2007
DOI: 10.1007/s10600-007-0222-y
|View full text |Cite
|
Sign up to set email alerts
|

NMR spectral analysis of flavonoids from Chrysanthemum coronarium

Abstract: analyses. 1-and 2-dimensional NMR spectroscopy of the rare naringenin 5-O-glucoside have been recorded and assigned for the first time. The flavonoid glucosides from Chrysanthemum coronarium showed week activity against Poliovirus I and Adenovirus type 7.Chrysanthemum coronarium L. (Compositae) is regarded in East Asia as a healthy vegetable because the edible portion contains abundant nutrients [1] as well as a fresh flavor [2]. This species is occasionally used as folk medicine [3] and has been found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The water-acetonitrile mixture containing compounds 1 (Velozo et al 1999) and 2 (Ibrahim et al 2007;Shimoda et al 2010), was subjected to slow evaporation at room temperature, and afforded 1 as long white-needle crystals, with 2 isolated from the filtrate after solvent evaporation. Analysis of the LRESMS spectra of 1 indicated peaks at m/z 457 and 433, assigned to [M+Na] + and [M-H]respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The water-acetonitrile mixture containing compounds 1 (Velozo et al 1999) and 2 (Ibrahim et al 2007;Shimoda et al 2010), was subjected to slow evaporation at room temperature, and afforded 1 as long white-needle crystals, with 2 isolated from the filtrate after solvent evaporation. Analysis of the LRESMS spectra of 1 indicated peaks at m/z 457 and 433, assigned to [M+Na] + and [M-H]respectively.…”
Section: Resultsmentioning
confidence: 99%
“…and 5 were identified as apigenin-7-O-glucoside and luteolin-7-O-glucoside by comparing their physical and spectroscopic data (see Supplementary material) with those reported byErsoz et al (2002);Chiruvella et al (2007);Ibrahim et al (2007) and Kuruuzum-Uz et al…”
mentioning
confidence: 82%
“…Many previous studies have reported the isolation, identification, and the biological activities of the plant. The results have shown that flavonoids [2], phenolic acids [3], sesquiterpene lactone [4], monoterpene [5], diterpene [6], glycosyldiglycerides [7], alkaloid [8], phytosterol [9], heterocyclic compounds [8], polyacetylenes [9], and essential oils [10,11] were the major chemical constituents present in the plant. Ch.…”
Section: Introductionmentioning
confidence: 99%
“…coronarium L., which are also the main bioactive constituents of the Compositae family [2,3]. Caffeoylquinic acids (CQAs) are cinnamate conjugates, which are biosynthesized through the phenylpropanoid pathway.…”
Section: Introductionmentioning
confidence: 99%